INTERNALISASI SIFAT WAJIB RASULULLAH DALAM PENGUATAN ETIKA PROFESI GURU DI ERA DIGITAL - Silmi Afifah; Inas Farrah Dina Noor; Arsya Ma’wa Ni’matul Izzati; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the internalization of the obligatory traits of Prophet Muhammad, shiddiq, amanah, tabligh, and fathanah, as a foundation for strengthening teachers’ professional ethics in the digital era. This topic is important because digital transformation has changed educational practices and expanded teachers’ ethical responsibilities. Teachers are no longer only responsible for delivering learning materials in the classroom, but also for guiding students in using digital media wisely, verifying information, maintaining academic honesty, protecting students’ privacy, and communicating ethically in online learning spaces. This study employed a qualitative approach with a library research design. The data sources consisted of relevant literature, including books, journal articles, regulations, and previous studies related to Islamic education, prophetic traits, teacher professional ethics, and digital education. The research instrument used was a documentation guide to identify, classify, and analyze key concepts from the selected sources. Data were analyzed using content analysis through the stages of data reduction, categorization, interpretation, and conclusion drawing. The results show that shiddiq strengthens teachers’ honesty and academic integrity; amanah reinforces responsibility in carrying out educational duties; tabligh supports ethical and educative communication; and fathanah encourages teachers to be intelligent, adaptive, and wise in using digital technology. The study concludes that the internalization of the obligatory traits of Prophet Muhammad can serve as a moral and spiritual foundation for developing teachers who are professional, ethical, and relevant to the challenges of digital education.